UNDERGRADUATE STUDENTS’ PERSPECTIVES IN USING EDMODO AS AN EDUCATIONAL SOCIAL NETWORK - Hikmah Nur Insani; Didi Suherdi; Gin Gin Gustine (English Review: Journal of English Education, 2018)
The integration of technology in education and the need to meet the requirements of the 21st century learning lead educators to use online learning platforms. Edmodo is offered as one of learning platforms that could be used in EFL classroom. This research aims to investigate perception of undergraduate students on the use of Edmodo as an educational social network which has been implemented in the classroom. This study employed mix method design by involving 50 undergraduate students from a university in Bandung, Indonesia. The data were collected through closed-ended and open-ended questionnaires. As results, it was found that undergraduate students showed positive response and attitudes towards the use of Edmodo in their learning process. Besides, some obstacles of using Edmodo were also revealed, such as lack of experiences in using technology and how to manage the time allocation. Finally, it is suggested that Edmodo should be implemented in undergraduate EFL classroom.Keywords: Edmodo, undergraduate students’ perception, educational social network, online learning platform